The body and consent in psychology, psychiatry, and medicine: a therapeutic rape culture - Tosh, Jemma (Routledge, 2020)
Cover; Half Title; Title; Copyright; Dedication; CONTENTS; Acknowledgements; 1 Introduction; 2 Intersex youth: non-consensual surgeries and nosocomial sexual abuse; 3 Queer and trans youth: 'sexual rehearsal play' and reparative therapies; 4 'Sex' as treatment: consent, coercion, and sex therapy; 5 Penetration as 'treatment': the pathologisation of sexual avoidance and pain; 6 Phallometrics: quantifying sexuality and sexual violence; 7 Conclusions: a therapeutic rape culture; References; Index